Defect engineering in antimony selenide thin film solar cells. (27th October 2022) - Wijesinghe, Udari; Longo, Giulia; Hutter, Oliver S.
Abstract : The complicated and unconventional defect chemistry of Sb2 Se3 largely dictates photovoltaic device performance. This comprehensive review aims to increase understanding of defect engineering, which is essential for further efficiency improvements. Abstract : Antimony selenide (Sb2 Se3 ) has gained promising attention as an inorganic absorber in thin-film photovoltaics and water splitting devices due to its excellent optoelectronic properties, low toxicity, and earth abundancy. Presently, Sb2 Se3 solar cells have a record power conversion efficiency of 10.12%, with a rapid rise over the past few years. However, further efficiency increases are hindered by the severe open circuit voltage deficit associated with the defects and interfacial recombination. The existing defects impact charge carrier generation, transportation, intrinsic electrical conductivity, and film crystallinity which inevitably influences the efficiency and stability of polycrystalline Sb2 Se3 solar cells. Thus, effective defect engineering aiming at understanding the chemical nature of defects is essential to enhance the inferior performance and functional properties of Sb2 Se3 thin films. Herein, a comprehensive review of the defect chemistry at surfaces, grain boundaries, and interfaces in Sb2 Se3 solar cells, and efforts made in the community to passivate these defect states are presented. Finally, the potential challenges associated with an in-depth understanding of defect dynamics and strategies to achieve highly efficient and stable Sb2 Se3 solar cells in the future are provided.